Effect of information, motivation, and behavioral skills model on adherence to medication, diet, and physical activity in HIV/ADIS patients: A health promotion strategy - Mahboobe Ameri; Ehsan Movahed; Jamileh Farokhzadian (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Adherence to treatment is one of the major challenges in patients with HIV/ADIS. If the patients do not adhere, they will face recurrent consequences, such as disease progression. The aim of this study was to investigate the effect of information, motivation, and behavioral Skills (IMB) model on medication adherence, diet adherence, and physical activity in HIV/ADIS patients. MATERIALS AND METHODS: This interventional study was conducted on 122 patients with 20 years of age and over with HIV/AIDS in Kerman City, Iran, in 2018. A total of patients were selected by census method and categorized into the intervention and control groups. Later, a researcher-made questionnaire on IMB was used before and 3 months after the intervention to assess medication adherence, diet adherence, and physical activity .The intervention study consisted of at least 8 training sessions (90 min) over a 12-week period. RESULTS: In adherence to medication, information (P = 0.034) and personal motivation (P = 0.003) constructs and in adherence to diet, information (P = 0.025), personal motivation (P = 0.001), self-efficacy (P = 0.010), and skills (P = 0.011) were significantly different between the two groups after the intervention (P = 0.011). However, regarding the adherence to physical activity, no significant difference was found between the two groups after the intervention. CONCLUSIONS: The IMB model can be effective in promoting the diet adherence in HIV/AIDS patients. In this regard, more qualitative and quantitative studies are recommended on the adherence to medication and physical activity.